2005
DOI: 10.1007/s11746-005-1081-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stability of soybean oil fatty acid methyl esters by oil stability index (OSI)

Abstract: Biodiesel, an alternative diesel fuel derived from transesterification of vegetable oils or animal fats, is composed of saturated and unsaturated long-chain FA alkyl esters. During long-term storage, oxidation caused by contact with air (autoxidation) presents a legitimate concern with respect to monitoring and maintaining fuel quality. Extensive oxidative degradation may compromise quality by adversely affecting kinematic viscosity, acid value, or PV. This work examines the oil stability index (OSI) as a para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 34 publications
2
59
0
2
Order By: Relevance
“…26 It is one of the most important methods in the measurement and evaluation of the oxidation of biodiesel, and many works report its use. 6,18,23,[27][28][29][30][31][32][33][34][35][36][37] The European standard for biodiesel quality (EN 14214) uses the Rancimat method, developed by Hardon and Zürcher, for measuring oxidative stability. 34 At present, Metrohm is the company that manufactures the Rancimat ® equipment used for this method.…”
Section: Techniques For Evaluating the Oxidation Of Biodieselmentioning
confidence: 99%
See 1 more Smart Citation
“…26 It is one of the most important methods in the measurement and evaluation of the oxidation of biodiesel, and many works report its use. 6,18,23,[27][28][29][30][31][32][33][34][35][36][37] The European standard for biodiesel quality (EN 14214) uses the Rancimat method, developed by Hardon and Zürcher, for measuring oxidative stability. 34 At present, Metrohm is the company that manufactures the Rancimat ® equipment used for this method.…”
Section: Techniques For Evaluating the Oxidation Of Biodieselmentioning
confidence: 99%
“…14,40 The acidity is also increased when the water that remains in the biodiesel causes the hydrolysis of esters, producing free fatty acids. 14,28 Acidity is a parameter regulated by international standards for biodiesel. European (EN 14214) and American standards (ASTM 6751) limit maximum values to 0.5 and 0.8 mg KOH g -1 , respectively.…”
Section: Storage Stability Of Biodieselmentioning
confidence: 99%
“…31 In general, a maximum test temperature of 60ºC was recommended for testing any biodiesel derived from high-iodine value (IV > 110) feedstocks unless it has been treated with antioxidants. 29,51 Another earlier study recommended a maximum temperature in the range 75-90ºC for blends of biodiesel with jet fuel. However, corresponding peak maxima detected at 117, 18, and 5 min demonstrated that increasing degree of unsaturation decreases oxidation induction time (OIT).…”
Section: Effects Of Oxidation On Biodieselmentioning
confidence: 99%
“…Estes estudos geralmente mostram que a P-DSC tem a vantagem de aumentar o número total de moles de oxigênio presente na célula, permitindo a aceleração da reação a baixas temperaturas. 32 Talvez o primeiro estudo a examinar a oxidação de ésteres metílicos de ácidos graxos (biodiesel) tenha sido realizado por apontaram que a análise por P-DSC é uma técnica apropriada para verificação da atividade antioxidante em relação aos efeitos dos tipos e concentração dos antioxidantes na resistência relativa à oxidação do biodiesel. O objetivo do trabalho foi produzir biodiesel a partir de óleo de girassol e etanol anidro, caracterizá-lo quanto a alguns parâmetros físico-químicos estabelecidos pela Agência Nacional do Petróleo (ANP) e avaliar sua estabilidade oxidativa com adição de antioxi-ANP) e avaliar sua estabilidade oxidativa com adição de antioxidantes sintéticos.…”
unclassified